Is Seeing believing?:On the Content Validity of Video Recordings for Use in Criminological Research. Issue 7 (3rd July 2021) - Parry, Megan M.; Dario, Lisa M.; Moule, Richard K.
ABSTRACT: Video recordings of police-citizen interactions are becoming increasingly commonplace and accessible to the public. The ability of these recordings to expose multiple individuals to a single encounter makes them ideal for use in criminological research, though little is known regarding the content validity of these videos. Given how open to interpretation these recordings are, it is necessary to ensure the validity of video content. To address this issue, we suggest and demonstrate a multi-stage approach for validating this content. Using this approach, and an expert panel of police officers, this paper seeks to examines a basic methodological challenge of analyzing video-recorded behavior. This paper examines the concordance of perceptions across officers and video content using a multi-stage validation procedure: directed closed-ended questions, subjective ratings, and qualitative responses. Directed closed-ended questions and subjective response ratings indicated higher agreement among respondents in their video assessments, and were in accordance with initial researcher video categorizations. Open-ended response options resulted in less agreement about the content of recordings. Focusing on the content validity of video recordings is the first step for their better integration into criminological research. Our findings highlight the utility of one method of ascertaining this validity.